2020
DOI: 10.1371/journal.pone.0233372
|View full text |Cite
|
Sign up to set email alerts
|

Muscle transcriptome analysis identifies genes involved in ciliogenesis and the molecular cascade associated with intramuscular fat content in Large White heavy pigs

Abstract: Intramuscular fat content (IMF) is a complex trait influencing the technological and sensorial features of meat products and determining pork quality. Thus, we aimed at analyzing through RNA-sequencing the Semimembranosus muscle transcriptome of Italian Large White pigs to study the gene networks associated with IMF deposition. Two groups of samples were used; each one was composed of six unrelated pigs with extreme and divergent IMF content (0.67 ± 0.09% in low IMF vs. 6.81 ± 1.17% in high IMF groups) that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 134 publications
6
27
0
1
Order By: Relevance
“…A range from 92.80% to 94.50% of the reads mapped to the porcine reference genome was used ( Table S2 ). These results agree with the previous study carried out in the same tissue of pigs from the same population but in different individuals (except L7) [ 24 ] and with a study carried out in Semimembranosus muscle tissue on Large White pigs [ 32 ].…”
Section: Resultssupporting
confidence: 93%
“…A range from 92.80% to 94.50% of the reads mapped to the porcine reference genome was used ( Table S2 ). These results agree with the previous study carried out in the same tissue of pigs from the same population but in different individuals (except L7) [ 24 ] and with a study carried out in Semimembranosus muscle tissue on Large White pigs [ 32 ].…”
Section: Resultssupporting
confidence: 93%
“…Primary cilia are non-motile organelles that have been shown to play an important role as antennae to extracellular stimuli during embryogenesis [ 53 ], adipogenesis, and myofibrogenesis [ 54 ]. In our previous study, we found several genes related to primary cilia associated with intramuscular fat deposition [ 55 ], and NEDD9 may take part in this complex signaling pathway related to muscle and adipose tissue development in embryogenesis. Interestingly, the marker ASGA0031014 fell into an intronic region harboring several sequences recognized by FOXO transcriptional regulators.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, WGCNA was also employed to analyze a number of complex traits, such as feed efficiency ( Xu Y. et al, 2018 ; Banerjee et al, 2020 ; Carmelo et al, 2020 ), heat tolerance ( He et al, 2020 ), residual feed intake ( Liu H. et al, 2016 ), and obesity ( Kogelman et al, 2014 ). However, so far, only one study was found that have used WGCNA to analyze IMF content in Italian Large White pigs ( Zappaterra et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%